SISTEM DAN KEBIJAKAN PEMERINTAH DALAM PENGELOLAAN SAMPAH DI PASAR PORSEA - Jernih Sigalingging; Maruli Siregar; Junilius Zai; Albert Telaumbanua; Leo Irianto Pasaribu; Eben Oktavianus Zai (Merwinspy Publisher, 2025)
Waste management in traditional markets, such as Porsea Market in Toba Regency, North Sumatra, faces complex challenges due to high trading activities that generate organic and inorganic waste. If not managed properly, waste can have a negative impact on the environment, public health, and visitor comfort. The purpose of this service is to analyze the system and government policies in waste management in Porsea Market and implement a management program that involves various parties, including the local government, market managers, traders, and local communities. The method used is a participatory approach with stages of problem identification, socialization, program implementation, and monitoring and evaluation. The program included the provision of segregated waste bins, increased frequency of waste collection, and the formation of a market cleaning team. The results showed that the program succeeded in increasing community awareness in sorting waste, reducing piles of waste in the market area, and creating a cleaner and more comfortable market environment.